Potential Of Methylated Circulating Free DNA (CFDNA) In The Leptin Gene As A Biomarker For Type 2 Diabetes Mellitus - Novia Anjelina; Farizky Martriano Humardani; Sulistyo Emantoko Dwi Putra (Green Publisher Indonesia, 2025)
Type 2 diabetes mellitus (DMT2) is a chronic metabolic disorder characterized by insulin resistance and hyperglycemia, with an ever-increasing global prevalence. One of the risk factors for DMT2 is Gestational Diabetes Mellitus (GDM), which is the body's inability to regulate glucose during pregnancy which significantly increases the risk of developing DMT2 in the mother and her offspring. Among the various metabolic changes observed in GDM, leptin has been widely researched for its role in energy metabolism and insulin resistance. Leptin levels generally increase in obesity and GDM conditions, one of which is influenced by epigenetic mechanisms, including DNA methylation. Increased methylation in the leptin gene promoter region has been associated with decreased leptin expression, indicating a potential pathway linking GDM to DMT2 susceptibility in offspring. Given the importance of epigenetic roles, analysis of leptin DNA methylation patterns, particularly through non-invasive detection of placental cfDNA, has the potential to be a biomarker for detecting DMT2 risk from prenatal times. This approach not only offers early detection, but also opens up opportunities for more targeted preventive measures to lower DMT2 in the future.